Pemberdayaan Masyarakat Desa Kualu Nenas Riau Melalui Diversifikasi Pemanfaatan Kulit Nanas Menjadi Larutan Eco-Enzyme - Erna, Maria; Nazhifah, Siti; Erlinda, Sri (Unri Conference Series: Community Engagement, 2025)
This community service activity aims to empower the community in Kualu Nenas Village through the diversification of pineapple waste utilization as raw material to produce Eco-Enzyme (EE) solution products that are economically valuable and environmentally friendly. Interviews with the community revealed that pineapple peel waste had never been processed into products. In addition, piles of pineapple waste were found to be dumped directly on the ground, polluting the environment. This program was attended by 30 participants in the socialization stage and 15 participants in the practical training stage. The methods used consisted of socialization on the importance of pineapple peel waste management and training on Eco-Enzyme production with direct assistance. The satisfaction survey results showed that 90% of participants felt that the material was presented clearly and was easy to understand, while 77% felt motivated to produce Eco-Enzyme independently. In addition, 100% of participants claimed to have gained new knowledge about waste management. From an economic perspective, calculations show that each household can generate profits from producing Eco-Enzyme solution, which can be used as floor cleaner, fertilizer, and soap mixture. Thus, this program not only successfully improved participants' knowledge and skills but also has the potential to increase local community income.